Synthesis of biomedical relevant porphyrins - Atta, Yasser Mohamed Shaker Abdelrahman (Trinity College (Dublin, Ireland). School of Chemistry, 2007)
The research carried out in the present study focuses mainly on the synthesis of functionalized, unsymmetrically substituted porphyrins for potential applications in photodynamic therapy. Chapter 1 introduces the different classes of porphyrins and describes the most significant general methodologies employed for the synthesis of various classes of meso-substituted porphyrins. The symmetric porphyrin starting materials (A2-porphyrins) are easily prepared by simple condensation reactions of dipyrromethane and suitable aldehydes. These porphyrins are then functionalized by a nucleophilic aromatic substitution reaction (SnAr) with a wide variety of aliphatic, aromatic and functionalized organolithium reagents. Chapter 2 is concerned with an efficient synthesis of novel A2BC-porphyrins bearing highly reactive centers in substituents at the meso positions using corresponding functionalized organolithium reagents via two-step reactions.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin